Happiness included : Jan Brady and beyond - Plumb, Eve, 1958-; Wilkie, Marcia (Citadel Press Books / Kensington Publishing Corp., 2026)
"In this engaging, intimate memoir, Eve Plumb, America's most memorable middle child, Jan, on the iconic TV sitcom The Brady Bunch, tells the behind-the-scenes story of her Hollywood life as a child actor, her colorful and impressively versatile career over the past six decades, and the personal ups and downs along the way--complete with many photos from her private archives. Everyone knows the theme song from The Brady Bunch, the little TV sitcom about a big, blended family that became a pop culture phenomenon. Airing from 1969 to 1974, the show has been in constant reruns ever since, turning child actor Eve Plumb into an instantly recognizable star, along with her five Brady siblings. With insight and humor, Eve has put it all on the page, from her discovery at age 6 by a talent agent neighbor, winning the role at her very first audition, and being cast in treasured guest star roles in classic TV shows, such as Lassie, It Takes a Thief, and Family Affair, to the fun but chaotic filming of The Brady Bunch's unforgettable pilot. Eve's is the story of a lovely girl with 'hair of gold' who grew up to become a multitalented woman in the unpredictable world of show business, the arts, and beyond. Here, she dispels rumors, talks about her controversial role in the TV movie Dawn: Portrait of a Teenage Runaway, recounts the blessings and the blunders of reuniting with her Brady brothers and sisters in TV spin-offs, and describes the satisfaction of finding later success on Broadway, in feature films--and in her incredible life."--Book jacket flap.